Age as moderated influence on the link of spiritual and emotional intelligence with mental health in high school students - Shabani, Jafar; Hassan, Siti Aishah; Ahmad, Aminah; Baba, Maznah (Marsland Press, 2010)
This study examined whether, spiritual intelligence (SI) and emotional intelligence (EI) can be considered as predictor for mental health. The present investigation was also to test the moderating effects of age on the relationship of SI and EI with mental health among high school students. The participants in the study were 247 High school students (124 male and 123 female) in the age range of 14-17 years old, at the Gorgan City, north of Iran. Three valid and reliable instruments were used to assess SI, EI and mental health. Descriptive statistics, multiple and moderated regression analysis were used to analyses the data. The result demonstrated that mental health can be influences by SI and EI. In addition, the moderated effect of age on the relationship of SI and EI with mental health was not found.